2015
DOI: 10.1094/phyto-10-14-0270-r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Gene Identified in Pathotype 5 of the Clubroot PathogenPlasmodiophora brassicae

Abstract: Clubroot caused by Plasmodiophora brassicae is an important disease of crucifers worldwide. Isolates of the pathogen can be classified into pathotypes according to their pathogenicity on differential hosts. In this study, the presence or absence of all database-available nonhousekeeping P. brassicae genes (118 in total) were assessed by polymerase chain reaction (PCR) analysis in isolates belonging to five P. brassicae pathotypes (2, 3, 5, 6, and 8 according to Williams' differential set). One gene, designated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Even many strategies have been proposed for clubroot disease control, but the use of resistant cultivars is still believed to be most effective (Peng et al, 2014;Zhang et al, 2015). The experiment result here may lay a foundation to further research about P. brassicae.…”
Section: Discussionmentioning
confidence: 65%
“…Even many strategies have been proposed for clubroot disease control, but the use of resistant cultivars is still believed to be most effective (Peng et al, 2014;Zhang et al, 2015). The experiment result here may lay a foundation to further research about P. brassicae.…”
Section: Discussionmentioning
confidence: 65%
“…The results of this study indicated that P. brassicae completed the primary infection stage in the two resistant B. rapa hosts, and that the secondary zoospores produced following primary infection invaded the cortex. Similarly, Zhang et al (2015) reported that secondary infection occurred in clubroot susceptible and resistant hybrid canola cultivars by single-spore isolate. This may reflect the main pathotype from the field isolate invade the cortex of clubroot-resistant hosts.…”
Section: Discussionmentioning
confidence: 91%
“…Finally, PI dye solution was added to stain the nuclei, and the cells were placed on ice for 30.0 min. The nuclei were visualized by a microscope [ 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%